My funny family moves house - Higgins, Chris (London: Hodder Children's Books, 2014)
It's a tight squeeze as usual in the Butterfield house, and with baby Will's stuff taking up all the room it's getting even worse. Lucinda's house has ten times more room for her family than the squished Butterfields have! Mattie's Worry List gets bigger when Mum seems to be unhappy, and wants to move house. But moving house would mean moving schools - Mattie's worst Worry List come true!
Keywords: Children's stories